River Performance Assessment Model. (2017) - Wahyudi, Agus Hari; Suripin,; Suharyanto,
Abstract: The performance of a river is the capability of the river and river infrastructure efforts to achieve its planned objectives. River development objectives can generally be grouped into two areas, namely to drainage at high flow on the rainy season and to utilized flow reliability on the dry season. Question that should be answered is how much the performance of the river and how to determine the priority order of handling the improvement of the river performance. The method to assess the performance of the river was conducted in two groups: assessing the physical condition of the river, and the functioning of the river by using various indicators. The assessment of the river infrastructure functions carried out in accordance to the purpose of the infrastructure. The model of the assessment method which was developed is limited on the river function as a drainage infrastructure. Therefore the model is clarified to the physical condition, and drainage function in small rivers. They are Rivers Pepe, Dengkeng, Jlantah, and Samin which located in Surakarta, Sukoharjo, Karanganyar and Klaten districts. By knowing the value of the river performance indicator, it can be used to determine the river improvement priority sequence. The research result shows that that the river performance of Pepe is 73.87% while the rivers Dengkeng, Jlantah, Samin are 60.53%, 77.31%, and 87.78%. It is clear that the first priority of river improvement is Dengkeng river.